How Does Personality Type Moderate Intimacy of Coach-Athlete with Stress Level? - Bektiningtyas, Novita; Undarwati, Anna (Universitas Negeri Semarang, 2023)
The decline in Indonesian sports performance is considered to be due to athletes' stress in game situations. Athletes who lack mental toughness are perceived as negative and threatening stressors in a game environment. The coach-athlete relationship and personality type are likely to influence stress levels. As a result, the purpose of this study was to establish the relationship between coach-athlete closeness and stress levels in terms of personality types. This study is quantitative, with the subject of 182 athletes from Central Java. Based on the regression test calculation result, the modified R2 value is 0.694, while the Pearson correlation calculation value is 0.620. As a result, it may be stated that personality type moderates the relationship between coach-athlete closeness and stress levels. The findings demonstrate a negative relationship between coach-athlete intimacy and stress levels. That is, if the coach-athlete relationship is more intimate, the stress levels will be lower; conversely if the coach-athlete relationship is less intimate, the stress levels will be greater.